The Kentucky Harness Horse - McCarr, Ken, 1903-1977 (Book collections on Project MUSE., 1978)
This informative book shows how the influence of Kentucky Standard breeding spread across the nation and finally around the world. Here is the story of the horses and farms, the men and women who made it possible. Rich with anecdote and founded on a unique store of learning, it will delight both the newcomer to the sport and the lifelong devotee.